Efektifitas Cara Penugasan Terhadap Hasil belajar Siswa Kelas VB Pada Mata Pelajaran IPS Di MI Darunnajah 2 Cipining - Athi Irmayasari; Khairrina; Heri Dermawan; Arizqi Ihsan Pratama; Ahmad Farid (CV. ALIM'SPUBLISHING, 2023)
Abstract : This research was conducted with the aim of knowing how much influence the Recitation Method had on Student Learning Outcomes at MI Darunnajah 2 Cipining. Student Learning Outcomes can be used as a benchmark to assess whether education in a school is successful or not. While learning outcomes are influenced by various factors, one of which is the use of the Recitation Method by an educator in the learning process. The purpose of this study was to analyze and interpret the effect of the Recitation Method on Student Learning Outcomes at MI Darunnajah 2 Cipining. This study uses a questionnaire data collection technique (questionnaire), and documentation. The results of this study are that there is an effect of the Recitation Method on Student Learning Outcomes at MI Darunnajah 2 Cipining. It is evident from the results of hypothesis testing (temporary testing) using the Chi Square formula, the x count value is 54.5811 greater than the x significance table 5% with a value of 16.919 . As for the results of these calculations, the recitation method has a contribution or influence of 90.18% in influencing Student Learning Outcomes at MI Darunnajah 2 Cipining. Keywords: Effectiveness, method, learning outcomes, stu